An Asian study on clinical and psychological factors associated with personal recovery in people with psychosis - Lim, Madeline (2020)
Background: Despite the rising recognition of personal recovery, there is a lack of research on personal recovery in individuals with psychosis in Singapore. This study aims to evaluate the psychometric properties of the QPR-15 using the CHIME personal recovery framework and to examine its associations with clinical recovery factors. Methods: Sixty-six stable outpatients were recruited and assessed at two time points approximately 2 weeks apart. Convergent validity was examined through Spearman correlations with scores on CHIME-related psychological factors: connectedness (Ryff subscale- positive relations with others), hope (Herth Hope Index- abbreviated), identity (Ryff subscale- self-acceptance, Internalized Stigma of Mental Illness- Brief), meaning (World Health Organization Quality of Life Assessment-Brief Form), empowerment (Empowerment Scale). Pearson’s correlation was used to examine the test-retest reliability, while Cronbach’s alpha was used to examine internal consistency. The initial factor structure was evaluated via principal component analysis, Velicer’s minimum average partial (MAP) criteria, parallel analysis, and a scree plot. Spearman correlations and hierarchical multiple linear regression (controlling for age and gender) were employed to examine the association of clinical (symptoms and functioning) and psychological factors with the QPR-15. Results: The QPR-15 demonstrated convergent validity with all CHIME-related psychological factors (rs ranged from 0.472 to 0.687). Internal consistency was excellent (Cronbach’s alpha = 0.934), and test-retest reliability was adequate (r = 0.708). Initial factor structure evaluations revealed a one-factor model. Correlations of clinical factors with the QPR-15 were mostly low (rs ranged from − 0.105 to − 0.544) but significant, except for depressive symptoms (CDSS: rs = − 0.529 to − 0.544), while correlations were moderate for psychological factors. Clinical factors significantly explained 28.3–31.8% of the variance of the QPR-15. Adding psychological factors significantly increased the model variance at baseline (∆ adjusted R2 = 0.369, F change < 0.001) and at time point 2 (∆ adjusted R2 = 0.208, F change < 0.001). Conclusion: Our results provide preliminary evidence that the QPR-15 has adequate psychometric properties in Singapore and encompasses the CHIME personal recovery framework. In addition, our results suggest that clinical recovery and personal recovery are not substitutes for each other but rather are complementary, thereby promoting a more holistic evaluation of recovery in people with psychosis. Implications are discussed.